Effectofthereduction in BNDES disbursements in brazilianregions: shift-shareanalysisbetween 2010-2019 - Giuli Pedroso, Ludmila (Cadernos de Ciências Sociais Aplicadas, 2023)
This article aims to analyze a decomposition of the influx of BNDES disbursements destined to the activities of the manufacturing industry in the Brazilian regions between 2010 and 2019. Using the neo-schumpeterian approach, using the shift-share analysis method model by Esteban-Marquillas (1972) following Lee and Kim's (2009) guidelines based on BNDES disbursement data in the period. Based on the neoshumpeterian theoretical framework, the results show that the fall in resources from activities in the manufacturing industry directs investments in the regions to specialize in the Manufacture of Pulp and Paper Products, Manufacture of Other Transport Equipment and Manufacture of Products Food.